Case Report: Two Is Not (Always) Better Than One: Pyloric Gland Adenoma of the Gastric Cardia and Concurrent Neuroendocrine Cell Dysplasia Arising From Autoimmune Gastritis - Guerini, Camilla; Lenti, Marco Vincenzo; Rossi, Chiara; Arpa, Giovanni; Peri, Andrea; Gallotti, Anna; Di Sabatino, Antonio; Vanoli, Alessandro (Frontiers in Medicine, 2022)
Autoimmune gastritis is a chronic immune-mediated disorder characterized by varied clinical manifestations and that should be endoscopically managed over time, as the gastric atrophy contributes to microenvironmental alterations of the stomach milieu, and an increased cancer risk has been linked to this condition. Here, we report the unusual case of a woman who developed a cardiac high-grade pyloric adenoma in a context of previously undiagnosed autoimmune gastritis with synchronous neuroendocrine cell hyperplastic and dysplastic lesions.